ESESATAN DALAM PENGEMBANGAN TES UNTUK PENGUKURAN PENCAPAlAN HASIL BELAJAR PADA KURIKULUM BERBASIS KOMPETENSI - Subali, Bambang (Jurnal Cakrawala Pendidikan, 2016)
The validity and reliability of measuring instruments determine their quality. the implementation of ehe competency-based curriculum at schools has caused basic problems to solve concerning requirements to be fulfilled related to the validity and reliabilitu of such instruments. This article to discuss the fulfillment of the requirements concerning the validitu and reliability of tests usend to measure learning achievement in educational research, or, for the interest of education of the competency-based curriculum.